Research on Packet Loss Caused by EMC Interference in Train Network Control System - LI Changxian; LIN Yuwen; LI Tingxu; LI Zongliang (机车电传动)
EMI on the train will cause random interference to the communication of the train network control system, and then cause the packet loss of the network communication. The influence of EMC interference on the train communication network (TCN) was studied by building a simulation experiment platform of train network control system, focusing on the influence of electrostatic discharge immunity test and electrical fast burst immunity test on communication characteristics. Based on the experimental data, the variation trend of the TCN packet loss rate with the interference size was obtained, and the data was analyzed and modeled, then the TCN packet loss prediction model based on EMC interference was obtained.